Effect of corrosion on aluminium tailor welded blanks (similar material welding) - Muhammad Firdaus, Ab Moin (2013)
In this study, the effect of corrosion on aluminium tailor welded blank with similar metal of aluminium type AA 1100 with different thickness joint by using filler ER 4043 and filler ER 4047 was investigated. Tungsten Inert gas (TIG) was used for butt welding of the process. Corrosion test was tested in 3.5 % Sodium Chloride (NaCl) solution by immersed the specimen for 30 days. Microstructure of base metal (BM), fusion zone (FZ), and heat affected zone (HAZ) was study with image analyzer. Tensile properties of welded joint were investigated by tensile test and hardness of the FZ, HAZ and BM was obtained by Vickers hardness test. From the corrosion test result, it shows that specimen weld by filler ER 4047 has good corrosion resistance than specimen weld by filler ER 4043. The data observed also show that the hardness and tensile properties of welded joint did decrease after the corrosion test. Microstructure at the FZ, HAZ and BM also change with the existence of pitting corrosion